PENGARUH BRAND AMBASSADOR TERHADAP KEPUTUSAN PEMBELIAN ONLINE MELALUI BRAND AWARENESS PADA MEDIA SOSIAL INSTAGRAM - Hasnidar, Hasnidar; Irmayansari, Irmayansari; Rahman, Sundari (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to examine and analyze the influence of brand ambassador and brand awareness on purchase decisions, the influence of brand ambassador on brand awareness, as well as the influence of brand ambassador on purchase decisions through brand awareness, in the context of fashion/beauty products in Makassar City. The population of this research consists of university students in Makassar. The sampling technique used is probability sampling, with a total sample of 120 respondents. The data were analyzed using the Structural Equation Modeling (SEM) method. The results of the study are that brand ambassadors do not have a direct influence on purchasing decisions, brand ambassadors have a direct influence on brand awareness, brand awareness has a direct influence on purchasing decisions and brand ambassadors have an indirect influence on purchasing decisions through brand awareness.